The Extension of Traumatic Subdural Hematoma into the Interhemispheric Fissure Is Associated with Coagulation Disorders: A Retrospective Study - Sannwald, Lennart W.; Moskopp, Dag; Moskopp, Mats L. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background This study investigates the correlation of the radiologic sign of interhemispheric subdural hematoma (iSDH) in different injury patterns with clinical coagulation disorders. It is hypothesized that the presence of iSDHs is correlated with clinical coagulation disorders in patients with traumatic brain injuries and subdural hematoma (SDH).Methods Between January 1, 2020 and June 30, 2022, 154 patients with SDH were identified. Coagulation disorders were assessed using chart review and patients were divided into four groups: SDH without iSDH without further injuries (SDH), SDH with iSDH without further injuries (SDH + iSDH), SDH without iSDH with further brain injuries (Combi), SDH with iSDH with further injuries (Combi + iSDH). These four groups were formed under the assumption that isolated SDHs result from a highly specific trauma mechanism (rupture of bridging veins) in predisposed elderly patients, while combined brain injuries with SDH result from a severe global traumatic brain injury combining different pathophysiologic mechanisms often in younger patients. The groups were analyzed for patient demographics, clinical presentation, and association with coagulation disorders. The significance level was set at p < 0.005.Results The presence of an iSDH was associated with a higher likelihood of concomitant coagulation disorder or anticoagulants in cases of isolated subdural hemorrhage (56.8% of the population in SDH vs. 94.7% in SDH + iSDH, p < 0.005). This effect was not significant in the cases with combined traumatic brain injuries (33.3% in Combi vs. 53.6% in Combi + iSDH, p > 0.005).Conclusion Our data indicate a high positive predictive value (PPV = 94.7%) for coagulation disorders in traumatic SDH patients with iSDH without any further focal and diffuse brain injuries. We consider this a relevant finding since it hints at the presence of coagulation disorders and might be used in early hemostaseologic assessment and emergency management.
Keywords: traumatic brain injury; interhemispheric; subdural hematoma; coagulation disorder